Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T16:09:33+01:00
(3x-2y+9)*4 = 12x - 8y + 36
(4x-7y-7)(-2) = -8x + 14y + 14
-2(3a+1)+(4a-5) = -6a - 2 + 4a - 5 = -2a - 7
5(2x+3y)-(x-2y) = 10x + 15y - x + 2y = 9x + 17y




2(y+6)-4(y-6) = 2y + 12 -4y + 24 = -2y + 36
3(a-8)-(5-2a) = 3a - 24 - 5 + 10a = 13a - 29
2010-02-25T16:12:10+01:00
(3x-2y+9)*4=12x-8y+36
(4x-7y-7)(-2)=-8x+14y+14
-2(3a+1)+(4a-5)=-6a-2+4a-5=-2a-7
5(2x+3y)-(x-2y)=10x+15y-x+2y=9x+17y


2(y+6)-4(y-6)=2y+12-4y+24=-2y+36
3(a-8)-(5-2a)=3a-24-5+2a=5a-29